Peran Islamic Worldview dalam Penguatan Identitas Keislaman di Era Modern - Irsyad Mahardi Hanardika; Sumiran Sumiran (Lembaga Yasin AlSys, 2026)
The modern era, marked by globalization, the development of digital technology, and the intensity of cultural exchange, has influenced the construction of Islamic identity among Muslim communities, particularly through the emergence of value relativism, identity crises, and the weakening internalization of Islamic values among some Muslim generations. This study aims to analyze the strategic role of the Islamic worldview in strengthening Islamic identity in the modern era. This study employed a qualitative approach using the library research method. Data were obtained from scholarly literature, international journal articles, academic books, and relevant documents discussing the concepts of the Islamic worldview and Islamic identity. The data were analyzed using content analysis techniques and critical interpretation of various scholarly sources. The findings show that the Islamic worldview functions as a conceptual foundation in shaping Muslims’ perspectives on God, human beings, knowledge, morality, and social life. Strengthening Islamic identity can be realized through the integration of tawhid values in education, the enhancement of digital-based Islamic literacy, the revitalization of Islamic intellectual culture, character development based on morality, and the development of critical awareness of the influence of global culture. The conclusion of this study affirms that the Islamic worldview has a strategic role in building an Islamic identity that is strong, adaptive, and relevant to the dynamics of modern society. The implications of this study provide a theoretical contribution to the development of Islamic educational thought and serve as a practical reference for educational institutions, families, and society in strengthening the Islamic identity of Muslim generations in the contemporary era.